A Comparative Study of Gauss-Seidel and Newton-Raphson Methods in Power Flow Analysis - Samburi, Nurfaraliyana; MOHAMAD NOR, AHMAD FATEH (Multidisciplinary Applied Research and Innovation, 2025)
The comprehensive study highlights the growing demand for electricity driven by global population growth, making the stability and efficiency of electric power systems increasingly critical. With global electricity demand predicted to rise significantly by 2050, the stability and efficiency of electric power systems have become a key challenge.  Power flow analysis is fundamental in addressing these challenges, particularly with voltage levels and overall system performance. In this research, a comparative analysis of the Gauss-Seidel (GS) and Newton-Raphson (NR) methods was conducted to assess their effectiveness in solving power flow problems. MATLAB simulations were utilized to perform the analysis on the IEEE 57-bus test system. According to the result obtained, the GS method is more suitable for smaller, and simpler power systems due to its computational efficiency, while the NR method provides superior accuracy and is more appropriate for large-scale systems. The findings indicate that the NR method is the most appropriate for performing the 57-bus test system. The novelty of this research is based on the evaluation of both methods under varying load conditions for a larger-scale system, offering significant insights into their applicability in voltage profile analysis. Overall, the findings emphasize the importance of selecting the appropriate method to ensure the accuracy and reliability of power system operations.